2010
DOI: 10.5483/bmbrep.2010.43.1.046
|View full text |Cite
|
Sign up to set email alerts
|

Protection of burn-induced skin injuries by the flavonoid kaempferol

Abstract: Thermal burn injury induces inflammatory cell infiltrates in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Several reports have shown that thermal burn injury induces inflammatory cell infiltration in the dermis as well as thickening of the epidermis (1)(2)(3)(4)(5)38). Here, we report that infiltration of inflammatory cells in the dermis as well as thickening of the epidermis are increased by LPS or CpG-DNA treatment at thermal injury-induced burned areas of skin in mice (Fig.…”
Section: Effects Of Lps and Cpg-dna On Thermal Injury-induced T Cell supporting
confidence: 54%
See 2 more Smart Citations
“…Several reports have shown that thermal burn injury induces inflammatory cell infiltration in the dermis as well as thickening of the epidermis (1)(2)(3)(4)(5)38). Here, we report that infiltration of inflammatory cells in the dermis as well as thickening of the epidermis are increased by LPS or CpG-DNA treatment at thermal injury-induced burned areas of skin in mice (Fig.…”
Section: Effects Of Lps and Cpg-dna On Thermal Injury-induced T Cell supporting
confidence: 54%
“…Previously, we showed that thermal injury-induced macroscopic appearances of lesions are spontaneously healed after 21 days via regeneration and repair (scar formation) (38). Therefore, we examined the effect of LPS and CpG-DNA on the injury-induced macroscopic appearances of lesions over 14 days.…”
Section: Immunostimulatory Effects Of Lps and Cpg-dna Upon Thermal Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are insufficient data to provide conclusive evidence on the health effects of most flavonoids (Kay 2010), the in vivo effects of kaempferol have been shown in several animal models, such as allergic lung disease (Medeiros et al 2009), carrageenan induced rat air pouch model (Mahat et al 2010), thermal burn-induced skin injuries (Park et al 2010), and mouse model of osteosarcoma (Huang et al 2010b). These reports imply that kaempferol may have clinical application, especially the safety issue of kaempferol has been discussed (Lee et al 2009;Li et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, under daily treatment with 100 µL kaempferol in ethanol 100 µM for 10-30 d, the inflammatory cell infiltrates in the dermis and thickening of the epidermis in the burned area of skin were clearly ameliorated. 11) These results demonstrated the efficacy of kaempferol in thermal burn-induced skin injuries. Oral administration of kaempferol results in very low bioavailability (2%) because it exhibits an extensive first-pass metabolism.…”
mentioning
confidence: 57%